Development of A Steam-Based Learning Module to Enhance Scientific Writing Skills and Chemical Literacy in Chemical Bonding Material - Atikah Indriastuti; Harjono, Harjono (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Chemical bonding is frequently perceived as an abstract and challenging topic by high school students, often resulting in low chemical literacy and underdeveloped scientific writing skills. Conventional, teacher-centered instruction further exacerbates these issues by limiting opportunities for authentic inquiry and scientific communication. To address this gap, this study aimed to develop, validate, and evaluate the effectiveness of a STEAM-based (Science, Technology, Engineering, Arts, and Mathematics) learning module integrated with Project-Based Learning (PjBL) to enhance chemical literacy and scientific writing skills among senior high school students. The research employed a Research and Development (R&D) design using the 4D model (Define, Design, Develop, Disseminate). Participants included 64 students from two experimental classes (XI C1 and XI D1), 25 students from a control class (XI E1) at SMA Negeri 2 Gianyar, and 36 students from SMA Negeri 1 Jatinom for a limited trial. Data were collected through pretest–posttest assessments of chemical literacy, observation rubrics for scientific writing skills, and student and teacher response questionnaires. Expert validation yielded an average Aiken’s V index of 0.967, indicating high validity in content, language, presentation, and alignment with STEAM–PjBL principles. The limited trial demonstrated high practicality, with readability and usability rates of 92% and 91.23%, respectively. In the main implementation, the module proved highly effective: (1) students’ chemical literacy improved significantly, with a normalized gain (N-Gain) of 0.88 (high category), outperforming the control group (N-Gain = 0.69); and (2) scientific writing skills achieved a mastery level of 91.44% (very good category), with a mean score of 3.66 out of 4. Positive responses from students (90.08%) and teachers (96.87%) confirmed that the STEAM–PjBL module fostered an interactive, contextual, and meaningful learning experience. The findings indicate that the module meets the criteria of validity, practicality, and effectiveness, making it well-suited for implementation in chemistry classrooms particularly within Indonesia’s Merdeka Curriculum framework. This study offers a replicable model for integrating interdisciplinary, student-centered approaches to strengthen both conceptual understanding and scientific communication competencies.